Artisanal billfish fisheries: gender roles, challenges, and opportunities - Adisa, Sylvia; Kadagi, Nelly I.; Ater, Sarah; Wambiji, Nina; Okeri, Maorine N.; Serra, Renata (Frontiers in Marine Science, 2025)
Marine fishery sustainability depends, among others, on broader governance factors affecting fishery value chains, including the division and distribution of gender roles. This study investigates the roles of women in artisanal (billfish) fisheries in Kenya, identifies the constraints to their participation, and makes policy recommendations to enhance women’s contribution to the growth and sustainability of this important sector. Qualitative and quantitative data through surveys (n=25), semi-structured interviews(n=75), group discussions (n=104), and observations in the selected study sites on the Kenya coast show that key factors influencing women’s involvement are market access, financial resources, and skillsets. From a value chain approach, women primarily engage in secondary activities like processing and trading, while their involvement in primary roles, such as managing fishing crews, is minimal. Historical social, cultural, and economic barriers, including lower education levels and traditional gender roles, contribute to this disparity. Existing gender dynamics reinforce inequalities in resource access and decision-making. This study seeks to fill knowledge gaps regarding women’s participation in billfish fisheries in the Western Indian Ocean, using Kenya as a case study. While women are known to participate in sport and recreational fisheries, their roles in artisanal fisheries are underrepresented in research. The analysis underscores the need for context-specific policies to enhance women’s roles and for integrating gender considerations into fisheries management, so that women can become crucial stakeholders in billfish fisheries. Overall, the findings have significant implications for promoting gender equity and sustainable fisheries practices in artisanal fisheries in Kenya and beyond.